What drives repurchase retention in music training institutions? examining the roles of customer satisfaction, perceived value, and service quality. - Li Long; Liu Lijia (PLoS ONE)
The rise of quality education has led to increased attention on music training as a vital means of enhancing personal qualities. However, with numerous music training institutions competing in the market, distinguishing oneself has become an urgent challenge. This study explores the key factors influencing customers' willingness to renew their enrollment at music training institutions through a questionnaire survey. The questionnaire addresses various aspects, including customer expectations, perceived value, customer satisfaction, repurchase intention, teacher expectations, peer influence, service quality, and brand image. The findings reveal a significant positive correlation between customer satisfaction and repurchase intention, suggesting that enhancing customer satisfaction is crucial for promoting repurchase intention. Additionally, perceived value positively impacts both customer satisfaction and repurchase intention, indicating that customers are more inclined to repurchase when they believe the course's value justifies the investment. Customer expectations also play a vital role, positively affecting perceived value and overall customer satisfaction. Furthermore, service quality and brand image significantly influence both customer satisfaction and repurchase intention, emphasizing the importance of high-quality service and a positive brand image in customer decision-making. Although the direct impact of teacher expectations on customer satisfaction is relatively weak, improving interactions between teachers and students, along with providing personalized guidance, can indirectly enhance satisfaction. Lastly, the anticipated positive correlation between peer influence and perceived value was not supported, suggesting that the impact of classmates may be less direct compared to that of teacher expectations and service quality.